Adjarian’s Armenian dialectology (1911) : Translation and commentary - Dolatian, Hossep (Language Science Press, 2024)
Armenian is an Indo-European language. Alongside two varieties, there are countless non-standard dialects, many of which were were made extinct because of the Armenian Genocide. This book is an English translation of a monograph originally written in Armenian by Hrachia Adjarian: "Հայ Բարբառագիտութիւն" or "Armenian dialectology." The original monograph consisted of descriptions of 31 non-standard Armenian varieties. The present book is both a translation and commentary on this monograph. The translation includes paradigm tables, sound changes, morpheme segmentation, glossing, and IPA transcriptions.